Eat. cook. L.A. : notes and recipes from the City of Angels - Crapanzano, Aleksandra (Ten Speed Press, an imprint of the Crown Publishing Group, a division of Penguin Random House LLC, 2019)
Once considered a culinary wasteland, Los Angeles is now one of the most exciting food cities in the world. Like the multi-faceted, sprawling city itself, the food of Los Angeles is utterly its own, an amalgam of international influence, disposable income, glamour, competition, immigrant vitality, health consciousness, purity, and beach-loving, laid back, hip, unrestrained creativity. With 100 recipes pulled from the city's best restaurants but retooled for the home cook<U+2014>like Charred Cucumber Gazpacho, Roast Chicken with Spicy Harissa, Vietnamese Coffee Pudding, Blackberry Mint Mojito Ice Cream and Thai Basil Margaritas<U+2014>EAT. COOK. L.A.; Notes and Recipes from the City of Angels is both a culinary roadmap and a sophisticated insider's look at one of America<U+2019>s most iconic and fascinating cities.